Atomic dreams : the new nuclear evangelists and the fight for the future of energy - Tuhus-Dubrow, Rebecca (Algonquin Books of Chapel Hill/Little, Brown and Company, 2025)
"The inside story of how nuclear energy--long considered scary, controversial, and even apocalyptic--has become the hot topic of the climate debate, and perhaps a vital power source of the future."--Amazon.